Monte Carlo computation of photon energy spectra in central axis of flattened and unflattened beams and doses in critical organs in a water phantom model of prostate radiotherapy. (September 2022) - Matuszak, N.; Kruszyna-Mochalska, M.; Skrobała, A.; Konefał, A.; Ryczkowski, A.; Romański, P.; Piotrowski, I.; Kulcenty, K.; Suchorska, W.; Malicki, J.
Abstract: A thorough understanding of the energy spectra for clinical linear accelerators is essential in modern cancer treatment planning. We aimed to determine the radiation spectra and out-of-field doses in a water phantom under the conditions of prostate radiotherapy in beams with a flattening filter (FF) and without (FFF). Monte Carlo simulations were performed to determine the energy spectra and doses outside the irradiated volume. Doses were registered in locations corresponding to critical organs (kidneys, lungs, and thyroid) and the spectra was determined in the central axis (prostate gland). Simulations were conducted for 6 MV and 10 MV for FF and FFF beams. The out-of-field doses were calculated at selected points from the field edge for 6 MV photon beams (FF and FFF), and for 10 and 15 MV beams (FFF only). Compared to FF beams, we found that the mean energy for the photon spectra of FFF beams was lower. For 6 MV FF beams, the relative doses for the critical organs (kidneys, lungs and thyroid) were 0.7%, 1.2%, 0.6% versus 1.6%, 1.2%, 1.3% for the unflattened beams. For 10 MV FF beams, the out-of-field doses to the organs were 0.1%, 0.4% and 0.4% versus 0.4%, 0.2% and 0.3% with the FFF beam. FFF beams had a higher photon fluence, indicating less scattered radiation. Removal of the filter leads to lower doses in the areas surrounding the irradiated volumes, especially at large distances from the treatment field. These findings are consistent with previous reports, indicating that flattening filter free beams are likely to improve clinical outcomes. The reduction in scattered radiation lowers the probability of inducing second cancers. Highlights: Monte Carlo simulations determine the energy spectra and doses outside the irradiated volume. The mean energy for the photon spectra of flattening filter free is lower compared to flattening filter beams. The scattered radiation reduction limit the probability of inducing second cancers.